Transcriptional Suppression of In Vitro-Integrated Human Immunodeficiency Virus Type 1 Does Not Correlate with Proviral DNA Methylation - Pion, Marjorie (American Society for Microbiology, 2003)
Persistence of human immunodeficiency virus type 1 (HIV-1) constitutes a major obstacle in the control of HIV-1 infection. Here we investigated whether the CpG methylation of the HIV-1 promoter can directly influence the expression of the HIV-1 genome and thereby contribute to the persistence and latency of HIV-1. The levels of CpG methylation in the promoter of HIV-1 were studied after bisulfite-induced modification of DNA in five Jurkat clonal cell lines transduced by an HIV-1 long terminal repeat (LTR)-driven retroviral vector and expressing enhanced green fluorescent protein (GFP) and in primary resting memory T cells challenged with HIV-1 or with an HIV-1-derived retroviral vector. Basal HIV-1 promoter activities were low or undetectable in three tested HIV-1 LTR-GFP clones, one of which encoded the Tat protein, and they reached medium or high levels in two other clones. The CpG dinucleotide that occurred in a latently infected clonal cell line 240 nucleotides upstream of the transcription start remained methylated after reactivation of HIV-1 transcription with 10 nM phorbol-12-myristate-13-acetate. In two clones showing a medium promoter activity and in resting memory T cells, the HIV-1 LTR was generally not methylated. Our results show that the methylation profiles of the HIV-1 LTR, including those present in latently infected cells, are low and do not correlate with the transcriptional activity. We suggest that, in a noncloned cellular population in which the HIV-1 proviruses are randomly integrated in the human genome, HIV-1 latency is imperfectly controlled by CpG methylation and is inherently accompanied by residual replication.